2012
DOI: 10.1177/0363546512448318
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology, Morbidity, and Outcome of Soccer-Related Fractures in a Standard Population

Abstract: Most patients sustaining a fracture while playing soccer will return to soccer at a similar level. While over one third of them will have persisting symptoms 2 years after injury, for the majority, this will not impair their soccer ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 21 publications
4
58
0
1
Order By: Relevance
“…Robertson et al found that at an average of 8.9 weeks, 77% of soccer players were able to return to the same level of play [21]. In the subset of professional athletes, this reached 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robertson et al found that at an average of 8.9 weeks, 77% of soccer players were able to return to the same level of play [21]. In the subset of professional athletes, this reached 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty percent of these fractures were soccer related (n = 112), with soccer being the most popular sport in the region [15]. Robertson et al encountered 367 soccer-associated fractures in athletes of varying skill levels, 73 (20%) of which were distal radius fractures, in a 1-year period [21]. They found rugby-associated distal radius fractures to be less common, with only 11 encountered in a 2-year period [22].…”
Section: Epidemiology Of Distal Radius Fractures In Athletesmentioning
confidence: 99%
“…Given the importance of such outcomes, this data would prove very useful in guiding management of injured soccer players. The currently available literature analyses combined cohorts of sport and soccer fractures, failing to take account of the influence of fracture site and severity on outcome (3,24). The evidence suggests that operatively managed fractures take longer to return to full level sport and have higher rates of persisting symptoms but this is likely influenced more severe fractures and lower limb fractures having higher rates of surgery (3).…”
Section: Discussionmentioning
confidence: 99%
“…Fractures remain one of the most serious injuries suffered by athletes, resulting in considerable time away from sport, with significant rates of persisting symptoms posttreatment (1)(2)(3)(4)(5). Despite their significant morbidty, there remains considerable variation in their management, due to various factors such as clinician preference and experience, difference in availability of resources and variation in patient desires and expectations (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation